Application of Mössbauer Spectroscopy in the Study of Copper Oxides - Панжиев Х.Ў (Peerian Journals Publishing, 2022)
One of the main problems of modern physics is the problem of determining the effective charges of atoms and the spatial distribution of electronic defects in the lattices of HTS. The definition of these values is necessary both to create the theoretical foundations of the technology for obtaining HTS with a given set of electrophysical properties
Keywords: obtaining; HTS; electrophysical; necessary